Carcinomatous pleuritis and pericarditis accompanied by pulmonary tuberculosis. Issue 6 (31st October 2016) - Hara, Munechika; Iwakami, Shin‐ichiro; Matsumoto, Naohisa; Miyawaki, Taichi; Wada, Ryo; Takahashi, Kazuhisa
Abstract : Although both lung cancer and pulmonary tuberculosis (TB) commonly occur in clinical practice, little attention has been paid to their coexistence. A 62‐year‐old female was admitted with acute dyspnoea secondary to cardiac tamponade. During her admission, a mass lesion harbouring air bronchograms in the right upper lobe rapidly increased in size. Surgical lung, pericardial, and pleural specimens yielded TB from a nodule in the right upper lobe and lung adenocarcinoma from the pericardium and pleura. Anti‐tuberculous therapy was administered and gefitinib was subsequently started after the positive identification of epidermal growth factor receptor (EGFR) mutation (exon 19 deletion). The patient's general condition gradually improved with the anti‐tuberculous and the EGFR‐tyrosine kinase inhibitor (EGFR‐TKI) treatment. Dual pathology is important to consider in patients with atypical radiological appearances. In those with proven EGFR mutation positive for lung cancer and pulmonary TB, sequential anti‐tuberculous medication followed by EGFR‐TKI treatment is advised. Abstract : Although both lung cancer and pulmonary tuberculosis (TB) commonly occur in clinical practice, little attention has been paid to their coexistence. This study reports a case of coexisting lung cancer and pulmonary TB treated with epidermal growth factor receptor (EGFR)‐tyrosine kinase inhibitor (TKI) and anti‐tuberculous therapy.